Role of Women in Tribes and Community Development: Challenges and Empowerment of Tribal Women in India (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The tribal population of India as a whole has suffered from several types of oppression,including land and resource alienation. Although though tribal women live outside of the mainstream ofnational life, they are not immune to the effects of the socioeconomic shifts that are reshaping the countryas a whole. The tribal woman's independence, influence over the traditional productive system, home,family, and maybe even life are all at risk as a result of this process of transformation. Very few women'svoices have been captured to show how they really feel about the many economic roles they play. In anutshell, it is accepted that women must be valued according to their specific circumstances. Womenshoulder a disproportionate share of society's burdens and duties due to their dual roles as caretakersof homes and communities. If women embrace their competitive edge as they enter womanhood, effortsto achieve gender parity will not be in vain.